The VraSR regulatory system contributes to virulence in Streptococcus suis via resistance to innate immune defenses - Peixi Chang; Weitian Li; Guolin Shi; Huan Li; Xiaoqing Yang; Zechen Xia; Yuan Ren; Zhiwei Li; Huanchun Chen; Weicheng Bei (Taylor & Francis, 2018)
Streptococcus suis is a highly invasive pathogen that can cause sepsis and meningitis in pigs and humans. However, we have limited understanding of the mechanisms S. suis uses to evade innate immunity. To investigate the involvement of the two-component signal transduction system of S. suis in host immune defense, we examined the expression of 15 response regulators of S. suis following stimulation with polymorphonuclear leukocytes (PMNs). We found that several response regulators were significantly up-regulated including vraR. Thus, we constructed an isogenic deletion mutant of vraSR genes in S. suis and demonstrated VraSR promotes both bacterial survival in human blood and resistance to human PMN-mediated killing. The VraSR mutant was more susceptible to phagocytosis by human PMNs and had greater sensitivity to oxidant and lysozyme than wild-type S. suis. Furthermore, in vitro findings and in vivo evidence from a mouse infection model together strongly demonstrate that ΔvraSR had greatly attenuated virulence compared with wild-type S. suis. Collectively, our data reveal that VraSR is a critical regulatory system that contributes to the survival of S. suis and its ability to defend against host innate immunity.
Keywords: Space Science; Medicine; Microbiology; Cell Biology; Genetics; Ecology; Immunology; Biological Sciences not elsewhere classified; Cancer; Hematology; Infectious Diseases; Virology